Herpes Zoster in Persons Living with HIV-1 Infection: Viremia and Immunological Defects Are Strong Risk Factors in the Era of Combination Antiretroviral Therapy - Erdmann, Nathaniel B.; Prentice, Heather A.; Bansal, Anju; Wiener, Howard W.; Burkholder, Greer; Shrestha, Sadeep; Tang, Jianming (Frontiers in Public Health, 2018)
In a cohort of 4,225 persons living with HIV-1 infection (PLWH) enrolled at a southeastern United States clinic, the overall rate of incident herpes zoster (HZ) was 101 per 10,000 person-years (PY) between January 1999 and January 2017, which nearly quadruples the rate reported for the general US population. In the same cohort, median age of HZ diagnosis was 39.5 years (interquartile range 31.5-49.2) in African American (AA) and 39.1 years (interquartile range 34.9-45.2) in European American (EA) PLWH, with the highest incidence seen in PLWH who were over 50 years old (144 and 93 per 10,000 PY in AA and EA, respectively, P = 0.18), showing no bias between men (100 per 10,000 PY) and women (101 per 10,000 PY). In multivariable models that were applicable to 245 HZ cases and 3,713 controls, age, nadir CD4+ T-cell (CD4) count, plasma viral load (VL), and duration of combination antiretroviral therapy were independent correlates of incident HZ (adjusted P ≤0.006 for all). Regardless of other factors, viremic PLWH (VL >50 copies/ml) were at the highest risk of HZ (adjusted odds ratio >3.0, P <0.0001). PLWH with nadir CD4 count ≥500 cells/µl showed relatively low risk (adjusted OR = 0.48, P = 0.003). In contrast, similar risk estimates were observed with three advancing age groups (30-39, 40-49 and ≥50) when compared with age <30 (adjusted OR = 1.86-2.17, P ≤0.010). These findings indicate that efforts for HZ diagnosis and prophylaxis should target viremic PLWH who are over 30 years old and with CD4 count <500 cells/µl.